1991
DOI: 10.1073/pnas.88.23.10926
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible familial Creutzfeldt-Jakob disease associated with five, seven, and eight extra octapeptide coding repeats in the PRNP gene.

Abstract: The PRNP gene, encoding the amyloid precursor protein that is centrally involved in Creutzfeldt-Jakob disease (CJD), has an unstable region of five variant tandem octapeptide coding repeats between codons 51 and 91. We screened a total of 535 individuals for the presence of extra repeats in this region, including patients with sporadic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
184
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(199 citation statements)
references
References 35 publications
13
184
1
1
Order By: Relevance
“…The genetic mechanism for the generation of the three extra repeats is probably unequal crossover, as described previously for other mutations with different numbers of insertion. 21 Identical mutation was also found in her mother but not in her father or a half-brother with a different mother. The girl's maternal grand parents died when they were in the six decades of life, and no medical record is available.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The genetic mechanism for the generation of the three extra repeats is probably unequal crossover, as described previously for other mutations with different numbers of insertion. 21 Identical mutation was also found in her mother but not in her father or a half-brother with a different mother. The girl's maternal grand parents died when they were in the six decades of life, and no medical record is available.…”
Section: Resultsmentioning
confidence: 96%
“…All insertion mutations have been found to be pathogenic, with the exception of one single case of an individual with four extra repeats, this 63-years-old patient died of liver cirrhosis without history of neurological illness. 21 The earliest disease onset for an insertion mutation was reported in a US family with seven extra repeats. The age at onset was between 23 and 35 years, and the duration of disease ranged from 10 to 15 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep have one additional allele with four octapeptides (six repeats in total) [78], and goats have one additional allele with only one octapeptide (three repeats in total) [33]. It has been shown that a total number of repeats above eight is associated with increased risk to Creutzfeldt-Jakob disease, a human form of TSE [28,66]. In contrast the relevance of a repeat variation between three and seven, found in ruminants, to TSE susceptibility has not yet been fully resolved.…”
Section: Octapeptide Polymorphismsmentioning
confidence: 99%
“…Transmissible spongiform encephalopathy (scrapie) is observed in several animal species, such as sheep, goats, minks, mule, deer and cattle ('mad cow disease'), and the disease has been transmitted to mice and hamsters in the laboratory. [91][92][93][94] All evidence indicates that human spongiform encephalopathies such as kuru, 95 Creutzfeld-Jakob disease, 96 Gerstmann-Sträussler-Scheinker disease, and fatal familial insomnia follow the same pathogenetic pattern as the animal diseases. 97,98 Trans-species infections between animals and from humans to monkeys are well known.…”
Section: Comparative Prion Reseachmentioning
confidence: 99%